PENGARUH DIMENSI SOSIAL, SUMBER DAYA MANUSIA DAN BAHAN BAKU TERHADAP JUMLAH PENGRAJIN PADA INDUSTRI GERABAH DESA GAMPANGSEJATI KECAMATAN LAREN KABUPATEN LAMONGAN: PENGARUH DIMENSI SOSIAL, SUMBER DAYA MANUSIA DAN BAHAN BAKU TERHADAP JUMLAH PENGRAJIN PADA INDUSTRI GERABAH DESA GAMPANGSEJATI KECAMATAN LAREN KABUPATEN LAMONGAN - Yenni Vera Fibriyanti; Noer Rafikah Zulyanti (Jurnal Mantik, 2019)
Research on the Effect of Social Dimensions, Human Resources and Raw Materials on the Number of Craftsmen in the Pottery Industry in Gampangsejati Village, Laren Subdistrict, Lamongan Regency aims to analyze the influence of social dimensions, human resources and raw materials partially and simultaneously on the number of craftsmen in the pottery industry in Gampangsejati Village, District Laren, Lamongan Regency. The type of data used in this study is primary data obtained from 20 Gampangsejati pottery craftsmen through questionnaires. The data is processed using SPSS version 20.0. The sampling technique in this study uses a saturated sampling technique, which is a sampling technique if all members of the population are used as samples. The results of the study revealed that social dimension variables, human resources and raw materials had a partial effect on the number of craftsmen in the pottery industry. This can be seen from the significance of less than 0.05 so Ho is rejected and Ha is accepted. From the results of the simultaneous test it is known that the significance of F <0.05 (0.001 <0.05) so that Ho is rejected and Ha is accepted. This shows that all independent variables (social dimensions, human resources, and raw materials) have a simultaneous influence on the decline of the pottery industry in the village of Gampangsejati, Laren Subdistrict, Lamongan Regency.